2015
DOI: 10.7314/apjcp.2015.16.16.6825
|View full text |Cite
|
Sign up to set email alerts
|

Review and Current Status of Opisthorchis viverrini Infection at the Community Level in Thailand

Abstract: Opisthorchis viverrini is remains a public health problem inThailand, particularly in the northeast and north regions which have the highest incidences of chonalgiocarcinoma (CCA). O. viverrini causes the disease opithorchiasis, and its has been classified as a group 1 biological carcinogen. Humans, dogs, and cats become infected with O. viverrini by ingesting raw or undercooked fish containing infective metacercariae. The first human cases of O. viverrini infection were reported in Thailand 100 years ago, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Chronic infection caused by the Southeast Asian liver fl uke (Opisthorchis viverrini) is a critical risk factor for the development of the bile duct cancer cholangiocarcinoma (CCA), what is a major health concern in South-East Asia (Thailand, Laos People's Democratic Republic, Cambodia and central Vietnam) Aunpromma et al, 2012;Miyamoto et al, 2014;Kaewpitoon et al, 2015;Khuntikeo et al, 2016). In Thailand at least 6 million people are estimated to be currently infected (Andrews et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic infection caused by the Southeast Asian liver fl uke (Opisthorchis viverrini) is a critical risk factor for the development of the bile duct cancer cholangiocarcinoma (CCA), what is a major health concern in South-East Asia (Thailand, Laos People's Democratic Republic, Cambodia and central Vietnam) Aunpromma et al, 2012;Miyamoto et al, 2014;Kaewpitoon et al, 2015;Khuntikeo et al, 2016). In Thailand at least 6 million people are estimated to be currently infected (Andrews et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of CCA has been reported that Nakhon Ratchasima province has 13.67-16.2 per 100,000 populations (Sripa et al, 2011). In addition, Opisthorchis viverrini; the carcinogenic liver fluke, also has been reported in this province (Kaewpitoon et al, 2012c;Kaewpitoon et al, 2015). Furthermore, the infective stage of O. viverrini was found frequently coverage areas approximately 78.1% of province (Kaewpitoon et al, 2012a).…”
Section: Discussionmentioning
confidence: 95%
“…Facilitate Health Literacy Regarding Carcinogenic Human Liver Fluke: A Randomized Controlled Trial in Thailand people are at risk of liver fluke infection (Sithithaworn et al, 2012), which has been found to have the highest prevalence in the northeast (16.6%) and north (10%) (Wongsaroj et al, 2014). The infection is frequently found in men over 35 years of age and in agricultural occupations (Kaewpitoon et al, 2015). The infection results from the consumption of raw or undercooked freshwater cyprinoid fish.…”
Section: Ovcca Web Application As Supplementary Materials Tomentioning
confidence: 99%